Faktor-Faktor Yang Mempengaruhi Tingkat Kesejahteraan Petani Tembakau Di Kecamatan Lengkong Kabupaten Nganjuk - Ika Kristie Febri Amalia; Enis Muzaroh; Mike Nur Widyanti (Fakultas Pertanian, Universitas Darul Ulum, 2025)
Lengkong Subdistrict, particularly Ketandan,Ngringin, and Jati Villages, is the largest tobacco production centre in Nganjuk Regency. Despite high tobacco production, farmers' welfare has not beenfully achieved due to various factors such as processing and marketingthat are not yet optimal. This study aims to analyse the influence of income, education, and land area on the welfare of tobacco farmers in Lengkong SubdistrictLengkong. A total of 50 respondents were selected using random sampling techniques, anddata was collected through a Google Form questionnaire. Data analysis was performedusing SPSS 26.0. The results showed that the income variablesignificantly influenced farmers' welfare,as indicated by a t-value of 2.429 and a significance level of 0.022. Meanwhile,the variables of education (t count 1.702) and land area (t count 0.503) did nothave a significant effect because the significance value was greater than 0.05. The simultaneous test showed that the three variables together had an effecton farmer welfare with a calculated F value of 11.070, which was greaterthan the table F. Among all the variables, income had the highest Standardised Coefficients Beta value, making it the most dominant factorinfluencing the welfare of tobacco farmers in Lengkong Subdistrict